Reagan [videorecording (Blu-Ray + DVD)] - Klausner, Howard; Quaid, Dennis; Miller, Penelope Ann; Voight, Jon, 1938-; Dillon, Kevin; Henrie, David, 1989-; Suvari, Mena, 1979-; Kengor, Paul, 1966- (Lionsgate, 2024)
Dennis Quaid delivers a tour-de-force performance as 40th U.S. President Ronald Reagan in this cinematic journey that encapsulates the spirit of the American dream. From his small-town roots to the glitter of Hollywood where he meets actress Jane Wyman and Warner Brothers' studio president Jack Warner, Reagan's incredible story culminates in obtaining the presidency with the support of his loving wife Nancy. Told through the voice of a former KGB agent (Oscar winner Jon Voight), Reagan offers a unique perspective as it is captivating.